Prokaryotic Expression of α-13 Giardin Gene and Its Intracellular Localization in Giardia lamblia - Yu, Xingang (Biomed Res Int, 2017)
To study prokaryotic expression and subcellular localization of α-13 giardin in Giardia lamblia trophozoites, α-13 giardin gene was amplified and cloned into prokaryotic expression vector pET-28a(+). The positive recombinant plasmid was transformed into E. coli BL21(DE3) for expression by using IPTG and autoinduction expression system (ZYM-5052). The target protein was validated by SDS-PAGE and Western blotting and purified by Ni-NTA Resin. Rabbits were immunized with purified fusion proteins for preparation of polyclonal antibody; then the intracellular location of α-13 giardin was determined by fluorescence immunoassay. The results showed that the length of α-13 giardin gene was 1038 bp, encoding a polypeptide of 345 amino acids. The expressed product was a fusion protein with about 40 kDa largely present in soluble form. The target protein accounted for 21.0% of total proteins after being induced with IPTG, while it accounted for 28.8% with ZYM-5052. The anti-α13-giardin polyclonal antibody possessed good antigenic specificity as well as excellent binding activity with recombinant α-13 giardin. Immunofluorescence assays revealed that α-13 giardin was localized in the cytoplasm of G. lamblia trophozoite, suggesting that it is a cytoplasm-associated protein. The present study may lay a foundation for further functional research on α-13 giardin of G. lamblia.